Hydrogen sulfide responsive nanoplatforms: Novel gas responsive drug delivery carriers for biomedical applications - Jiafeng Zou; Zeting Yuan; Xiaojie Chen; You Chen; Min Yao; Yang Chen; Xiang Li; Yi Chen; Wenxing Ding; Chuanhe Xia; Yuzheng Zhao; Feng Gao (Elsevier, 2024)
Hydrogen sulfide (H2S) is a toxic, essential gas used in various biological and physical processes and has been the subject of many targeted studies on its role as a new gas transmitter. These studies have mainly focused on the production and pharmacological side effects caused by H2S. Therefore, effective strategies to remove H2S has become a key research topic. Furthermore, the development of novel nanoplatforms has provided new tools for the targeted removal of H2S. This paper was performed to review the association between H2S and disease, related H2S inhibitory drugs, as well as H2S responsive nanoplatforms (HRNs). This review first analyzed the role of H2S in multiple tissues and conditions. Second, common drugs used to eliminate H2S, as well as their potential for combination with anticancer agents, were summarized. Not only the existing studies on HRNs, but also the inhibition H2S combined with different therapeutic methods were both sorted out in this review. Furthermore, this review provided in-depth analysis of the potential of HRNs about treatment or detection in detail. Finally, potential challenges of HRNs were proposed. This study demonstrates the excellent potential of HRNs for biomedical applications.